Self administered medical abortion pills: evaluation of the clinical outcome and complications among women presenting with unsupervised pill intake to a tertiary care hospital in Malwa region of Punjab, India - Bhalla, Shivali; Goyal, Lajya Devi; Bhalla, Shivam; Kaur, Balpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Unsupervised medical abortion pill intake is becoming a public health hazard. Because of its widespread misuse, we planned to undertake this study to evaluate the clinical presentation and outcome of such patients. Methods: Hundred patients meeting inclusion criteria were included. Clinical presentation, treatment given and, outcome and complications were analyzed. Results: Majority (53%) patients were aged between 30-39 years. Seventy-seven percent were gravida three or more. Only 26% had taken the pill within prescribed gestational age limit for MTP (<seven weeks). Mid-trimester pill intake was encountered in 13 % patients. Pill was consumed without any prior medical consultation by 73% patients. Majority (49%) presented with incomplete abortion requiring surgical evacuation. Anaemia was most common associated co-morbidity in 80% patients and 28% required blood transfusions. Twenty-four percent patients presented with life threatening shock. Sepsis was noted in 3% patients. Emergency laprotomy was required in 11% cases. Continuation of pregnancy was reported in 13% patients. Unintended pregnancy and failure of contraception were main reasons cited for abortion by 38% and 26% women. Non-contraceptive users constituted 48% patients . Over the counter easy availability was the main reason for unsupervised pill intake in 58% cases. Conclusions: Unauthorized over the counter pill availability despite legal ban and ignorance of women have led to increased number of unsafe abortions. Strict legislations need to be imposed. Increasing awareness among women regarding complications of unsupervised pill intake and easy availability of safe contraceptive methods can help control this problem.